Lower plasma protein C activity is associated with early myocardial necrosis and no-reflow phenomenon in patients with ST elevation myocardial infarction. Issue 4 (4th July 2019) - Stankovic, Suncica; Obradovic, Slobodan; Dzudovic, Boris; Djenic, Nemanja; Romanovic, Radoslav; Jovic, Zoran; Spasic, Marijan; Djuric, Obrad; Malovic, Dragana; Stavric, Milena; Subota, Vesna
Abstract: Background: Activity of protein C has important role in the development of early necrosis and no-reflow phenomenon in patients with ST-segment elevation myocardial infarction (STEMI) after successful primary percutaneous coronary intervention (pPCI). Methods: We examined association between plasma activity of protein C, antithrombin, coagulation factors II, VII, VIII and fibrinogen to early formation of new Q-waves (myocardial necrosis) before pPCI and early ST-segment resolution (microcirculatory reperfusion) after pPCI in patients with acute STEMI. According to ischaemic time, patients were considered as early or late presenters. 12-lead ECG was analysed for the presence of new Q-wave at admission and for significant ST-segment resolution 60 minutes after primary PCI. Results: In early presenters' group, protein C activity was significantly lower in patients who did not achieve significant ST-segment resolution after pPCI compared to patients who did (1.11 IU/L vs. 0.99 IU/L, p  = .006) and in patients who had new Q-waves compared to group who had not (1.04 UI/l vs. 1.11 IU/L, p  = .038). There was significant negative correlation between protein C activity and maximal CK-MB levels ( R 2  = 0.06, p  = .009) and BNP levels ( R 2  = 0.109, p  = .003) and significant positive correlation between protein C activity with LVEF ( R 2  = 0.065, constant = 33.940, b  = 11.968, p  = .007) in early STEMI presenters. There were no differences between the activity of other examined haemostasis factors. Conclusion: Therefore we concluded that STEMI patients with early myocardial necrosis and no-reflow phenomenon after pPCI have lower activity of plasma protein C levels.